Efforts to Improve Science Learning Achievement on the Material Characteristics of Living Things Through the Application of Task-Based Learning in Third Grade Students - Suparti, Suparti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to improve the learning achievement of Natural Science material on the characteristics of living things in class III students in semester 1 of SD Negeri 1 Mireng in the 2019/2020 academic year through the application of Task-Based Learning. This study used the form of Classroom Action Research which was carried out in 2 (two) cycles, conducted at SD Negeri 1 Mireng with the research subjects of all third grade students of SD Negeri 1 Mireng, Trucuk District, Klaten Regency semester 1 of the 2019/2020 School Year, totaling 28 students. The research method uses Classroom Action Research. Data collection is done through observation, documentation and tests. Data analysis was carried out with 3 (three) stages including data reduction, data presentation and conclusion drawing or verification. From empirical data obtained through the application of Task-Based Learning can improve the learning achievement of students in the material of the characteristics of living things from the initial condition of the average daily test score of 61 with a completeness rate of 35.7% to the final condition with an average score of 84 with a completeness rate of 100% in cycle II in third grade students of SD Negeri 1 Mireng semester 1 of the 2019/2020 school year. It is concluded that through the application of Task-Based Learning (TBL) can improve the learning achievement of science material on the characteristics of living things in third grade students of SD Negeri 1 Mireng Semester 1 of the 2019/2020 academic year.